1998
DOI: 10.1177/136346159803500204
|View full text |Cite
|
Sign up to set email alerts
|

Suicide and Gender in the People's Republic of China, Taiwan, Hong Kong, and Chinese in the US

Abstract: In this paper we conduct a comparison of the rates of suicide for men and women across four settings: the People's Republic of China (PRC), Taiwan, Hong Kong, and Asian groups in the US. The rates for rural PRC women are the highest, followed by urban PRC, Hong Kong, Taiwan, and at the lowest rate, US Asians. The highest rates for men were found in the rural PRC setting, followed by Hong Kong, Taiwan, Asians in the US, and the lowest rate was found in the urban PRC. The high rate among women in rural PRC setti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 17 publications
0
11
1
Order By: Relevance
“…Suicidal ideation and attempt were lowest in Hanoi (2.3% and Ͻ1%, respectively), Shanghai (8.1% and 1.3%, respectively), and highest in Taipei (17.0% and 6.9%, respectively). Although existing literature suggests that overall youth in China experience higher rates of suicide compared with youth in Taipei and Hanoi [8,20], in this study, youth from Taipei reported the highest prevalence of suicidal thoughts and attempt. A possible explanation for this finding is the different meaning of suicide across contexts.…”
Section: Discussioncontrasting
confidence: 50%
“…Suicidal ideation and attempt were lowest in Hanoi (2.3% and Ͻ1%, respectively), Shanghai (8.1% and 1.3%, respectively), and highest in Taipei (17.0% and 6.9%, respectively). Although existing literature suggests that overall youth in China experience higher rates of suicide compared with youth in Taipei and Hanoi [8,20], in this study, youth from Taipei reported the highest prevalence of suicidal thoughts and attempt. A possible explanation for this finding is the different meaning of suicide across contexts.…”
Section: Discussioncontrasting
confidence: 50%
“…In contrast, if the reason for suicide is related to societal needs, such as loyalty to the family or community, then suicide is more accepted by his or her family because he or she saves face for the great self. From this perspective, suicide is viewed as a shameful act, bringing dishonor to a family, and also an honorable act, upholding ethical standards in Chinese culture (Shiang, Barron, Xiao, Blinn, & Tam, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Suicide in China is a relatively new topic, with studies increasing across the past two decades (Zhang, Shuhua, Wieczorek, & Jiang, 2002). However, most of the studies have been published in Chinese journals and have provided only limited and regional data, given the short history of suicide research; only a few have appeared in Englishlanguage journals (Lee, Tsang, Li, Phillips, & Kleinman, 2007;Phillips, Li, & Zhang, 2002;Phillips, Yang, et al, 2002;Phillips, Yang, Li, & Li, 2004;Ran, Wu, Conwell, Chen, & Chan, 2004;Shiang, Barron, Xiao, Blinn, & Tam, 1998;Wong, Stewart, Ho, & Lam, 2007;Zhang, Conwell, Zhou, & Jiang, 2004;Zhang, Tong, & Zhou, 2005;Zhang, Zhou, Grabiner, & Li, in press).…”
Section: Suicide and Suicide Studies In Chinamentioning
confidence: 99%